Diosmin alleviates doxorubicin-induced chemobrain in rats via inhibition of oxido-inflammation, apoptosis and modulation of autophagy - Oyovwi O. Mega; Falajiki Y. Faith; Ohwin P. Ejiro; Joseph G. Uchechukwu; Olowe G. Temitope; Onome B. Oghenetega; Emojevwe Victor; Tesi P. Edesiri; Rotu A. Rume; Rotu A. Rotu; Oyeleke Abiodun Abioye; Okwute Patrick Godwin (Brain Disorders, 2024)
Background/aim: Doxorubicin (DOX) is a highly effective chemotherapy medicine commonly used to treat breast cancer; yet, despite its clinical efficacy, it usually causes chemobrain. As a result, we investigated the neuroprotective effects of Diosmin (DIOS) on DOX-induced chemobrain in male rat brains. Animals and methods: In the experimental protocol, Rats were divided into 4 groups: group I received solvent and saline for 56 days, group II received Dios and a concomitant dose of saline for 56 days, group III received DOX intraperitoneally on 7th, 14th, 21st, 28th, 35th, 42nd, 49th and 56th days, and Group IV received DIOS (40 mg/kg P.O.) for 56 days and DOX was administered one hour after DIOS oral administration. The novel-object recognition memory test (NORT) was used to assess non-spatial memory function. Following that, brain neurochemical status were assessed. Results: DIOS increased cognitive performance in DOX-treated rats by enhancing exploration of unfamiliar objects. DIOS protects the brain from DOX-mediated alterations in oxidative status, as well as brain metabolic enzyme indicators. It also decreased MMP-6, IL-6, IL-β1, TNF-α and COX-2 expression, reduced apoptotic markers levels, boosted mTOR protein levels, lowered beclin-1, restored brain metabolic enzyme activities, increased neurotransmitter as well as cathepsin levels, and avoided the rise in α-synuclein and PON1 enzyme activity. Conclusion: In conclusion, DIOS protects rats' brains against DOX-induced chemobrain via oxidative stress inhibition, autophagy modulation, and down-regulation of inflammatory and apoptotic markers.